1998
DOI: 10.1086/517810
|View full text |Cite
|
Sign up to set email alerts
|

Capsular Polysaccharide Types of Group B Streptococcal Isolates from Neonates with Early‐Onset Systemic Infection

Abstract: The distribution of serotypes of group B streptococci (GBS) isolated from 67 infants with early-onset sepsis are described. Case-infants were assembled from 13 hospitals across the United States from 15 July 1995 to 5 February 1997 through prospective active surveillance. The distribution of GBS serotypes was Ia, 40%; Ib, 9%; II, 6%; III, 27%; V, 15%; and nontypeable, 3%. Type V occurred more frequently in the northeast region (New York and New Jersey) than in other regions (29% vs. 9%, P = .06). Conversely, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
47
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 13 publications
9
47
1
1
Order By: Relevance
“…Our data are consistent with other reports on serotypes typically associated with human and bovine S. agalactiae infections. While serotypes I, II, and III were the most prevalent serotypes among isolates from human neonates with early-onset GBS infections in the 1970s (3), more recent studies have shown serotypes Ia and III are the most common serotypes currently associated with GBS infections among neonates (2,32). Serotype V strains emerged as a cause of human infections in 1985; these strains have been shown to currently cause the majority of GBS infections among nonpregnant adults in the United States (6,23).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with other reports on serotypes typically associated with human and bovine S. agalactiae infections. While serotypes I, II, and III were the most prevalent serotypes among isolates from human neonates with early-onset GBS infections in the 1970s (3), more recent studies have shown serotypes Ia and III are the most common serotypes currently associated with GBS infections among neonates (2,32). Serotype V strains emerged as a cause of human infections in 1985; these strains have been shown to currently cause the majority of GBS infections among nonpregnant adults in the United States (6,23).…”
Section: Discussionmentioning
confidence: 99%
“…Several serotypes of GBS exist (9), but only a few (serotypes Ia, Ib, Ic, II, and III) are common causes of human disease. Over the past decade, several investigators reported an increasing proportion of GBS disease to be due to serotype V (GBS-V) (1,2,8,11,21). During the same period, several investigators also reported an increase in macrolide (erythromycin) and clindamycin resistance among GBS isolates from U.S. hospitals (1,13,15,17).…”
Section: Pulsed-field Gel Electrophoresis (Pfge) Was Performed On 122mentioning
confidence: 99%
“…A serotype distribution based on the serotypes for one geographic location or small numbers of patients may not be generally applicable (9,17). Continued monitoring will be necessary to assess the suitability of combinations of GBS vaccine antigens for different target populations in different geographic locations (7,9).…”
mentioning
confidence: 99%